2020
DOI: 10.1002/1878-0261.12789
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinicopathological characteristics of ROS1‐rearranged non‐small‐cell lung cancers identified by next‐generation sequencing

Abstract: ROS1 gene rearrangements have been reported in diverse cancer types including non-small-cell lung cancer (NSCLC), and with a notably higher prevalence in lung adenocarcinoma. The tyrosine kinase inhibitors, crizotinib, lorlatinib, and entrectinib, have demonstrated favorable efficacy in treating ROS1-rearranged NSCLCs. Herein, we retrospectively reviewed 17 158 NSCLC patients whose tumor specimen and/or circulating cell-free DNA underwent comprehensive genomic profiling. A total of 258 unique patients were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 32 publications
5
31
0
Order By: Relevance
“…The fusion product retained the entire ROS1 tyrosine kinase domain. SDC4 is a common fusion partner of ROS1 , constituting for 13% of ROS1 fusion in Chinese patients, and intron 2 for SDC4 and intron 31 for ROS1 are common breakpoint point locations ( 14 ). Patients with SDC4-ROS1 rearrangement were enrolled into the clinical study to access the efficacy of crizotinib in NSCLC patients with ROS1 fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The fusion product retained the entire ROS1 tyrosine kinase domain. SDC4 is a common fusion partner of ROS1 , constituting for 13% of ROS1 fusion in Chinese patients, and intron 2 for SDC4 and intron 31 for ROS1 are common breakpoint point locations ( 14 ). Patients with SDC4-ROS1 rearrangement were enrolled into the clinical study to access the efficacy of crizotinib in NSCLC patients with ROS1 fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The results of several studies showed that the presence of CD74-ROS-1 rearrangement was associated with longer progression-free survival (PFS) and overall survival (OS) than non-CD74-ROS-1 rearrangement [36]. However, that association with survival was not found in other studies [34].…”
Section: Fusion Partnersmentioning
confidence: 98%
“…ROS-1 rearrangement occurs at a breakpoint in the ROS gene at the 5′ end of exons 32, 34, 35, or 36, or introns 31 or 33 [ 14 , 34 ]. The most frequently seen fusion partners ( Table 1 ) are CD74 (38–54%), EZR (13%–24%), SDC4 (9–13%), and SLC34A2 (5–10%) [ 34 , 35 ].…”
Section: Molecular Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations